51.5k views
3 votes
X+1/x-1-x-1/x+1=7/12​

User Btreat
by
5.0k points

1 Answer

2 votes

Given:

The equation is:


(x+1)/(x-1)-(x-1)/(x+1)=(7)/(12)

To find:

The value of x.

Solution:

Formulae used:


(a+b)^2=a^2+2ab+b^2


(a-b)^2=a^2-2ab+b^2


(a-b)(a+b)=a^2-b^2

We have,


(x+1)/(x-1)-(x-1)/(x+1)=(7)/(12)

Taking LCM, we get


((x+1)^2-(x^2-1)^2)/((x-1)(x+1))=(7)/(12)


(x^2+2x+1-(x^2-2x+1))/(x^2-1^2)=(7)/(12)

On cross multiplication, we get


12(x^2+2x+1-x^2+2x-1)=7(x^2-1)


12(4x)=7x^2-7


48x=7x^2-7


0=7x^2-48x-7

Splitting the middle term, we get


7x^2-49x+x-7=0


7x(x-7)+1(x-7)=0


(7x+1)(x-7)=0


x=-(1)/(7),7

Therefore, the values of x are
-(1)/(7) and
7.

User Rigo
by
5.1k points